2015
DOI: 10.1021/ol5034833
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Synthesis of Rapamycin Fragment To Build a Macrocyclic Toolbox

Abstract: A stereoselective synthesis of a rapamycin fragment is developed and further utilized toward building a macrocyclic chemical toolbox. The amino alcohol moiety embedded in the 22-membered macrocyclic ring allowed for the addition of a variation in the chiral side chain. The key reactions leading to the synthesis of the rapamycin-derived pyran fragment include the following: (i) Paterson aldol, (ii) stereoselective β-OH carbonyl reduction, and (iii) regio- and stereoselective intramolecular oxy-Michael reaction.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

5
3

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Due to numerous binding interactions and large ring size act as modulators of protein-protein and other types of biomolecular (e. g., DNA/RNA-protein) interactions. [60][61][62][63] Numerous recent review articles have discussed the role of macrocycles in medicinal chemistry, natural products, and synthetic macrocycles in drug discovery. [64,65] Due to several advantages over macrocycle, more than 100 marketed macrocycle drugs derived from natural products place in drug discovery [66] Some of the natural product macrocyclic drugs are erythromycin, cyclosporine, epothilone, rapamycin, etc.…”
Section: Macrocyclization Strategiesmentioning
confidence: 99%
“…Due to numerous binding interactions and large ring size act as modulators of protein-protein and other types of biomolecular (e. g., DNA/RNA-protein) interactions. [60][61][62][63] Numerous recent review articles have discussed the role of macrocycles in medicinal chemistry, natural products, and synthetic macrocycles in drug discovery. [64,65] Due to several advantages over macrocycle, more than 100 marketed macrocycle drugs derived from natural products place in drug discovery [66] Some of the natural product macrocyclic drugs are erythromycin, cyclosporine, epothilone, rapamycin, etc.…”
Section: Macrocyclization Strategiesmentioning
confidence: 99%
“…99,100 More recently, Arya and co-workers have synthesized rapamycin fragment-derived macrocycles 12.1. 101 As shown in the retrosynthesis (Scheme 12), Arya's team developed a stereoselective approach to the synthesis of rapamycinderived pyran fragment 12.2. The key reactions in their approach included the Paterson aldol reaction, stereoselective β-hydroxy carbonyl reduction and an intramolecular regioand stereoselective oxy-Michael addition.…”
Section: Synthesis and Biological Evaluation Of Rapamycin Analogsmentioning
confidence: 99%
“…Finally, the bis-allyl intermediates were treated with Grubbs' second generation catalyst giving rapamycin fragment-derived macrocycles 12.1(a-d) in good yields. 101 Molecular docking studies were performed with these macrocycles to predict key binding interactions with human immunophilin FKBP-12 and the FKBP12-rapamycin associated protein complexed with human immunophilin. The docking studies showed good binding interactions of rapamycin fragment-derived macrocycles with both targets.…”
Section: Synthesis and Biological Evaluation Of Rapamycin Analogsmentioning
confidence: 99%
“…[26][27][28][29][30][31][32] In the past few years, our group has reported the development of several methods for synthesizing diverse sets of macrocyclic compounds. 26,[34][35][36][37][38][39] The long-term goal of our current study is to assemble a macrocyclic chemical toolbox consisting of compounds originating from substructures of eribulin to permit the exploration of their biological properties in several challenging targets related to protein-protein interactions and deregulated signaling pathways.…”
Section: Special Topic Syn Thesismentioning
confidence: 99%